Chloroquine and Hydroxychloroquine for the Treatment of COVID-19: a Systematic Review and Meta-analysis - Elavarasi, Arunmozhimaran; Prasad, Manya; Seth, Tulika; Sahoo, Ranjit Kumar; Madan, Karan; Nischal, Neeraj; Soneja, Manish; Sharma, Atul; Maulik, Subir Kumar; Shalimar; Garg, Pramod (Journal of general internal medicine : JGIM, 2020)
Background There is no effective therapy for COVID-19. Hydroxychloroquine (HCQ) and chloroquine (CQ) have been used for its treatment but their safety and efficacy remain uncertain. Objective We performed a systematic review to synthesize the available data on the efficacy and safety of CQ and HCQ for the treatment of COVID-19. Methods Two reviewers searched for published and pre-published relevant articles between December 2019 and 8 June 2020. The data from the selected studies were abstracted and analyzed for efficacy and safety outcomes. Critical appraisal of the evidence was done by Cochrane risk of bias tool and Newcastle Ottawa Scale. The quality of evidence was graded as per the GRADE approach. Results We reviewed 12 observational and 3 randomized trials which included 10,659 patients of whom 5713 received CQ/HCQ and 4966 received only standard of care. The efficacy of CQ/HCQ for COVID-19 was inconsistent across the studies. Meta-analysis of included studies revealed no significant reduction in mortality with HCQ use [RR 0.98 95% CI 0.66–1.46], time to fever resolution (mean difference − 0.54 days (− 1.19–011)) or clinical deterioration/development of ARDS with HCQ [RR 0.90 95% CI 0.47–1.71]. There was a higher risk of ECG abnormalities/arrhythmia with HCQ/CQ [RR 1.46 95% CI 1.04 to 2.06]. The quality of evidence was graded as very low for these outcomes. Authors’ Conclusion The available evidence suggests that CQ or HCQ does not improve clinical outcomes in COVID-19. Well-designed randomized trials are required for assessing the efficacy and safety of HCQ and CQ for COVID-19.